Liquidity, volume, and volatility - Bogousslavsky, Vincent,Collin-Dufresne, Pierre (Swiss Finance Institute, 2019)
We examine the relation between liquidity, volume, and volatility using a comprehensive sample of U.S. stocks in the post-decimalization period. For large stocks, effective spread and volume are positively related in the time series even after controlling for volatility, contrary to most theoretical predictions. This relation is mostly driven by the systematic component of volume. In contrast, for small stocks the evidence matches the predictions of standard adverse selection models. In line with a continuous-time inventory model, we show that the volatility of order imbalances can reconcile our puzzling finding with standard intuition. Order imbalance volatility is strongly associated with spreads both in the time series and cross-section. Evidence from alternative liquidity measures (price impact and depth), spread decomposition, and intraday patterns support our interpretation of order imbalance volatility as a measure of inventory risk. Furthermore, order imbalance volatility is priced in the cross-section of weekly returns
10.2139/ssrn.3336171
Keywords: Graue Literatur; liquidity; volume; volatility; order imbalance; inventory risk; adverse selection